Working Capital Management and its Impact on Profitability: A Case of ACC Cement Companies of Coimbatore, Tamilnadu - Arumugam, Dr.A.; Sasikala., Mrs.M. (IJRDO - Journal of Business Management, 2016)
“In the present competitive environment all organisation are trying to cut the cost of product and also trying the improve the profitability of organisation, If working capital is sound then there will be minimum idle capital and ultimately it reduces the interest burden of organisation and it will help to improve the profitability of organisation”.